Treatment of vegetable oily wastewater using an integrated microfiltration-reverse osmosis system - Yu, Xiaoli (Water science and technology : a journal of the International Association on Water Pollution Research, 2010)
Vegetable oil processing plants and catering trade often generate a large amount of oil-containing wastewater, which causes serious environmental problems. The objective of this work was to explore the feasibility of vegetable oil wastewater treatment with an integrated microfiltration-reverse osmosis (MF-RO) process. The influence of operational parameters on the separation behaviors were investigated in MF process. In MF continuous process the steady flux was around 90 (L/m(2) h) when the concentrated multiple reached 16, and the oil content in permeate was less than 12 mg/L. In the RO continuous process, antifouling membrane was used to treat permeate from the ceramic membrane process in order to improve the water quality. The RO process had a permeate flux of 24 (L/m(2) h) and water recovery rate of 95%. The permeate from the RO stage was free of oil, and its TOC and conductivity were less than 0.6 mg/L and 50 micros/cm, respectively. The results demonstrated that the two stage membrane process combining MF and RO is highly efficient in the treatment of oil-containing wastewater